Celebrity of Instagram and Endorsements: Shaping and Constructing Social Identity - Zinaida, Rahma Santhi; Diantara, Eku; Amin, Zaid (Universitas Semarang, 2025)
Purpose: This research aims to explore how endorsements by celebrities on Instagram play a role in the formation and development of social identities among users. It will investigate the psychological processes, including relationships and the desire for social connection, that influence the link between celebrity impact and identity development. Methods: The method used was a qualitative descriptive method, data collection techniques by observations, interviews and documentations. Researchers choose influencers with high engagement rates. Key Informants that being choosen are three celebgram from Palembang, South Sumatera, Indonesia. Findings: A celebrity's social identity is shaped by their interactions with their fans, as seen by the quantity of views, comments, direct messages, re-posts, and mentions. Along with participation, interpersonal interactions, communication style, social relationships, lifestyle relevance, and the presence of online communities. The visual appearance of celebrities is a major factor in the success of product endorsements because visuals are the first element that attracts the audience's attention. Originality: The originality of this study stems from identifying a distinctive concept known as ‘Local Empathetic Communication’ as an essential element in forming social identity among celebgrams in Palembang. In contrast to prior research, this study combines the Social Construction of Reality Theory with the VisCap Model to illustrate that followers engage more deeply with influencers who embody local culture and values through empathetic and relatable dialogue. This emphasis on a localized emotional connection has not been previously addressed in earlier works, making it a new and significant contribution to the discipline.